Synthetic Peptides as Therapeutic Agents: Lessons Learned From Evolutionary Ancient Peptides and Their Transit Across Blood-Brain Barriers - Lovejoy, David A.; Hogg, David W.; Dodsworth, Thomas L.; Jurado, Fernando R.; Read, Casey C.; D'Aquila, Andrea L.; Barsyte-Lovejoy, Dalia (Frontiers in Endocrinology, 2019)
Teneurins are multifunctional transmembrane proteins that bind to the latrophilins, which are members of the Adhesion family of G-protein-coupled receptors (GPCR). Together, this ligand-receptor unit plays an integral role in synaptogenesis, neurological development and maintenance, and is present in most metazoans. The teneurins possess a cleavable peptide unit on their extracellular face that interacts with the latrophilins and plays a number of roles in the inhibition of the corticotropin-releasing factor (CRF) -associated stress response. This peptide, known as teneurin C-terminal associated peptide (TCAP), has structural similarity to CRF, and its related peptides, such as calcitonin and the secretin-based peptides. Moreover, its receptor, latrophilin is structurally related to the secretin family of GPCRs. TCAP is a soluble peptide that enters the brain and efficaciously regulates glucose transport into the brain. We posit that TCAP represents a phylogenetically older peptide system that evolved before the origin of the CRF-calcitonin-secretin clade of peptides and plays a fundamental role in the regulation of cell-to-cell energy homeostasis. Moreover, because TCAP is efficacious at blocking CRF action in vitro and in vivo, it may act as a phylogenetically older peptide system that evolved as a natural antagonist to the CRF-mediated stress response. Thus, TCAP’s actions on the CNS may provide new insights into the development of peptide therapeutics for the treatment of mood disorders.